Geographic variation and risk factors for systemic and limb ischemic events in patients with symptomatic peripheral artery disease: Insights from the REACH Registry. Issue 9 (18th May 2017) - Abtan, Jérémie; Bhatt, Deepak L.; Elbez, Yedid; Sorbets, Emmanuel; Eagle, Kim; Reid, Christopher M.; Baumgartner, Iris; Wu, David; Hanson, Mary E.; Hannachi, Hakima; Singhal, Puneet K.; Steg, Philippe Gabriel; et al.
Abstract : Background: Patients with symptomatic peripheral artery disease (PAD) are at high risk of ischemic events. However, data about predictors of this risk are limited. Hypothesis: We analyzed baseline characteristics and 4‐year follow‐up of patients enrolled in the international REduction of Atherothrombosis for Continued Health (REACH) Registry with symptomatic PAD and no history of stroke/transient ischemic attack to describe annual rates of recurrent ischemic events globally and geographically. Methods: The primary outcome was systemic ischemic events (composite of cardiovascular death, myocardial infarction, or stroke) at 4 years. The secondary outcome was limb ischemic events (composite of lower limb amputation, peripheral bypass graft, and percutaneous intervention for PAD) at 2 years. Multivariate analysis identified risk factors associated with recurrent ischemic events. Results: The primary endpoint rate reached 4.7% during the first year and increased continuously (by 4%–5% each year) to 17.6% by year 4, driven mainly by cardiovascular mortality (11.1% at year 4). Japan experienced lower adjusted ischemic rates ( P < 0.01) vs North America. Renal impairment ( P < 0.01), congestive heart failure ( P < 0.01), history of diabetes ( P < 0.01), history of myocardial infarction ( P = 0.01), vascular disease (single or poly, P < 0.01), and older age ( P < 0.01) were associated with increased risk of systemic ischemic events, whereas statin use was associated with lower risk ( P = 0.03). The limb ischemic event rate was 5.7% at 2 years. Conclusions: Four‐year systemic ischemic risk in patients with PAD and no history of stroke or transient ischemic attack remains high, and was mainly driven by cardiovascular mortality.